Design, Characterisation and Applications of Cellulose-Based Thin Films, Nanofibers and 3D Printed Structures: A Laboratory Manual - Pivec, Tanja; Mohan, Tamilselvan; Kargl, Rupert; Kurečič, Manja; Stana Kleinschek, Karin (2021)
The introduction of the Laboratory Manual gives the theoretical bases on cellulose and its derivatives, which are used as starting polymers for the preparation of multifunctional polymers with three different advanced techniques - spin coating, electrospinning and 3D printing. In the following, each technique is presented in a separate Lab Exercise. Each exercise covers the theoretical basics on techniques for polymer processing and methods for their characterisation, with an emphasis on the application of prepared materials. The experimental sections contain all the necessary information needed to implement the exercises, while the added results provide students with the help to implement correct and successful exercises and interpret the results.
Keywords: polysaccharides; cellulose; electrospun; spin-coating; 3D printing; nanofiber; thin films; multifunctional materials